Effect of BAU-Biofungicide, Neem Oil and a Nematicide on the Root-Knot (Meloidogyne javanica) of Papaya (Carica papaya) - Pradhan, MAA; Rahaman, MM; Paul, SK; Ahamad, MU; Goswami, BK (Bangladesh Journal of Agricultural Research, 2012)
In a pot experiment, BAU-Biofungicide (Trichoderma harzianum) neem oil and curaterr (carbofuran) 5G were tested against root-knot (Meloidogyne javanica) of two papaya varieties Kashempuri and Deshi papaya. Seedlings were inoculated with second stage larvae of M. javanica. Neem oil (5 ml/ 10g seeds) and BAU-Biofungicide (1:4) were used as seed treatant and curaterr as side dressing. Both the bio-agents significantly increased the root and shoot growth of papaya plant and reduction of galls and eggmasses and suppressed the development of J2, J3, and J4 and adult females of M. javanica. Efficacy of BAU-Biofungicide was to reduce the gall and nematode development and to increase plant growth was similar to nematicide curaterr. BAU-Biofungicide gave higher effect in most of the growth characters compared to neem oil and prevented the development of adult females and juveniles like nematicide curaterr. DOI: http://dx.doi.org/10.3329/bjar.v37i2.11230 Bangladesh J. Agril. Res. 37(2): 271-277, June 2012